MONITORING AND SURVEILLANCE OF MULTI-DRUG- AND EXTENSIVELY DRUG-RESISTANT TUBERCULOSIS - Zholdybayeva , E.V. (Eurasian Journal of Applied Biotechnology, 2022)
Multi-drug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) area major problem in Kazakhstan and, hence,new research initiatives and treatment protocols are urgently required.World-wide, diagnosis of TB is largely reliant on smear microscopy; however,this method has low sensitivity, which can also be further compromised in an endemic HIV setting. Moreover, smear microscopydoes not provide information on drug susceptibility or the genotype of the causative agent. At present, drug susceptibility is mainly tested using culture-based methods.However, the methodology is time-consuming and requires specialized infrastructure, and thus,in many countries,is restricted to large centers and does not always include testing for second-line drug resistance.An alternative approach is the TB-SPRINT assay, which reflects the idea of an “all-in-one” assay that identifies the causative agentand also identifieswith high confidence any mutations conferring resistance. The TB-SPRINT assaycan act as a surveillance tool to monitor the epidemiology of disease in communities and countries. An improved tuberculosis diagnostic assay and improved understanding of risk factors for spread of drug-resistant TB will benefit local populations and will indirectly be very beneficial to the economy of Kazakhstan.